PENGARUH ROA, ROE, Dan DER TERHADAP HARGA SAHAM PERUSAHAAN LQ45 DI BEI - Sesilia Rumondang Sinaga; Lestarinta Br Brahmana; Ledya Dacosta Sinaga; Ivan Jeremy H Silaban; Hamonangan Siallagan; Rizki Christian Sipayung (Jurnal Bisnis dan Kewirausahaan, 2023)
Capital market as a means of business financing where companies obtain capital from investors. The main purpose of investors buying shares to obtain dividends from the difference between the selling price and the purchase price. The share price is the price per share of the company issued on the stock exchange. This study aims to examine the relationship between Return On Assets, Return On Equity, Earning Per Share and Debt to Equity Ratio on stock prices conducted in all LQ45 companies listed on the Indonesia Stock Exchange during the 2016-2020 period. This study is a quantitative study that was tested using multiple linear regression through SPSS 25. The results of this study indicate that ROA has a positive effect because the rate of return is greater so that investors are interested in buying shares which will affect stock prices, the ROE has a negative effect. The higher the value of Return On Equity owned by a company, the lower the company's stock price, DER has a positive effect because the higher the DER value, the lower the stock price